The Dark That Matters: Long Non-coding RNAs as Master Regulators of Cellular Metabolism in Non-communicable Diseases - Mongelli, Alessia; Martelli, Fabio; Farsetti, Antonella; Gaetano, Carlo (Frontiers in Physiology, 2019)
Non-coding RNAs are pivotal for many cellular functions, such as splicing, gene regulation, chromosome structure and hormone-like activity. Here, we will report about the biology and the general molecular mechanisms associated with long non-coding RNAs (lncRNAs), a class of >200 nucleotides-long ribonucleic acid sequences, and their role in chronic non-transmissible diseases. In particular, we will summarize knowledge about some of the best characterized lncRNAs, such as H19 and MALAT1, and how they may impact on carbohydrate and lipid metabolism and/or protein synthesis and degradation. Evidence will be presented about how lncRNAs expression might affect cellular and organismal metabolism and whether their modulation could provide ground for the development of innovative treatments.